2017
DOI: 10.2136/sssaj2016.06.0199
|View full text |Cite
|
Sign up to set email alerts
|

Water Retention and Preferential States of Soil Moisture in a Cultivated Vertisol

Abstract: Core Ideas Water retention data from saturation to oven dryness were collected for a Vertisol. New water retention and differential water capacity models were developed. Draining of intra‐aggregate pore space triggers the dry field soil moisture state. Mode of the textural pore space controls shift to wet field soil moisture state. Vertisols are well suited for rainfed agriculture in water‐limited environments as a result of their unique water transfer and retention characteristics. Despite their importance, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 36 publications
2
14
0
Order By: Relevance
“…The data of this figure were estimated with the Kosugi water retention curve, whose results were similar to those computed with the van Genuchten equation, except for some soil samples of the Pedrera farm, whose retention curve did not show a clear air entry state. This property, also found in the SWRC of swelling soils of the zone [37], posed some problems to other authors [38]; Pierson and Mulla [13] suggested the addition of a second-degree polynomial to the van Genuchten water retention equation.…”
Section: Soil Quality and S Indexmentioning
confidence: 88%
“…The data of this figure were estimated with the Kosugi water retention curve, whose results were similar to those computed with the van Genuchten equation, except for some soil samples of the Pedrera farm, whose retention curve did not show a clear air entry state. This property, also found in the SWRC of swelling soils of the zone [37], posed some problems to other authors [38]; Pierson and Mulla [13] suggested the addition of a second-degree polynomial to the van Genuchten water retention equation.…”
Section: Soil Quality and S Indexmentioning
confidence: 88%
“…0 = log 10 (ϕ 0 ), ad = log 10 (ϕ ad ), and [-] is a smoothing parameter. Vanderlinden et al (2017) combined the double exponential model (Dexter, Czy, Richard, & Reszkowska, 2008) with the Groenevelt and Grant (2004) model to describe the full range of the water retention curve (EG model):…”
Section: Single-segment Modelsmentioning
confidence: 99%
“…This is particularly true in seasonally dry climates, where water‐limiting conditions persist during long periods and soil water content becomes the single most important control for numerous ecohydrological and biogeochemical processes that take place at or near the soil surface (Wang, Manzoni, Ravi, Riveros‐Iregui, & Caylor, 2015). Under such environmental conditions and in the light of climate change, clay soils become of prime importance for dryland agriculture as a result of their capacity to retain large amounts of water and supply it to crops under conditions of large atmospheric water demand (Vanderlinden et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Vanderlinden et al (2017) modelled a multimodal SWRC and the equivalent pore‐size distribution of a Vertisol, and related characteristic points of the SWRC with field‐measured preferential soil moisture state data. Jensen, Schjønning, Watts, Christensen, and Munkholm (2019) confirmed the need for such an approach by showing that unimodal pore‐size distributions cannot capture soil management effects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation